College Students' Perceptions on Performance-Based Assessment Use in Boosting Speaking Ability - Sebastianus Menggo; Tobias Gunas (International Journal of Language Education, 2022)
Assessment is one component of a learning process that cannot be excluded by an English teacher in the teaching-learning process. The form and type of assessment applied in the teaching-learning process are adapted to the orientation of learners’ target outcomes. It is recognized as a space of reflection for teachers and students in the awareness of shortcomings and achieving such learning goals. Performance-based assessment is one of the possible appropriate options for measuring all criteria fulfillment in the English speaking class. The present study aims to analyze the implementation of performance-based assessment and disclose students' responses to this assessment in the speaking class. This research is a quantitative descriptive study administered between November 2020 and January 2021 for three months. Participants (N=49) in this study were selected from two first-grade English Education Study Program classes, Universitas Katolik Indonesia Santu Paulus Ruteng. Speaking rubrics and questionnaires were the instruments used in collecting data. The data taken from these instruments were then analyzed with the Excel Chart Data Series software program's aid, accompanied by a qualitative interpretation from the data provided. The research findings show that the type of performance-based assessment affects increasing speaking ability (the post-test average = 76), and college students' perception of performance-based assessment use in speaking was primarily included in positive perception. The lecturers are encouraged to apply this type of assessment to their speaking class.